Pusat Informasi dan Pengembangan Pariwisata di Kabupaten Kebumen (Pendekatan Arsitektur Tropis) - Lupitasari, Lia; , Nur Rahmawati S, ST, MT (2016)
As a maritime country, Indonesia is the largest archipelago in the world that is passed by the equator. One of the economic sector in Indonesia is the field of tourism. Both cultural and natural wealth of Indonesia is the most important component of tourism. As in Kebumen one of which contained a lot of tourism potentials. Kebumen is one area with many attractions of interest include natural attractions and beaches. The southern part of Kebumen is lowland while the northern part of the mountains which is a series of mountains Serayu. In the southern area there are a series of limestone mountains Gombong that stretches to the south coast. Supported by the many tourist places in an area, the applicability of course need the role of local governments that run the government special tourism. Especially for the promotion of information activities and attractions that hold important implications for the interest and motivation of travelers to be more focused, planned, integrated to be realized effectively. With the Center for Information and Tourism Development, is expected to provide information, data, exhibitions, introduction of regional culture and makes it easier to access, learn and study the potential that exists in Kebumen and expected the public can obtain the desired information. By taking the approach to the concept of tropical architecture are expected to provide convenience for users / employees and for the tourists who come can also enjoy both the comfort of physical and non-physical comfort. In other words, the function of the Center for Information and Tourism Development is to create a container for activities related to research and development activities, arts and cultural information, but it is more important that as a tourist information center in Kebumen. How to create a tourism information center building design that has the character of the building with the approach of tropical architecture concept. Keywords: Tourism information, Kebumen, tropical architecture.